Gir Calves Growth Performance, Feed Intake and Micro-Climate Variation under Different Housing Modification System during Winter Season - Jat, Maya; Jat, Ram Prasad; Bhateshwar, Vinod; Paswan, Vinod Kumar; Nehra, Hanuman Lal (Indian Journal of Dairy Science, 2021)
The better scientific management of the calves during the growth phase ensures an optimal body growth rate and efficient feed conversion efficiency and has thus has a direct effect on the life time production and reproductive performance of dairy animals. This study investigated the Gir calves growth performance, feed intake and micro-climate variation under different housing modification system during winter season. Twenty-four healthy Gir calves of twelve months of age were randomly divided into three homogenous modified housing groups containing with eight calves in each group. Group GC-1: conventional barn (during night) + open paddock (during day), GC-2: conventional barn + rubber mat and GC-3: loose house + curtains. The concentrate supplements given 1.5 kg/calve/day as pellet feed, green lucerne (Medicago sativa) 2.5 kg/calve/day and wheat straw (Triticum aestivum) ad lib as dry fodder. During the statistical analysis, the mean minimum morning temperature (P